(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
The problem of forced convection heat transfer of supercritical CO2 in a horizontal channel is investigated numerically by a lattice Boltzmann method. This study is stimulated by our recent experimental findings on solar collectors using supercritical CO2 as a working fluid, which can achieve the collector efficiency high up to 70%. To deeply understand the heat transfer characteristics of supercritical CO2 and provide a theoretical guidance for improving our current experimental system, in present study several typical experimental flow conditions are simulated. In particular, the work focuses on the convective heat transfer characteristics of supercritical CO2 flowing in a horizontal channel with mediate Reynolds numbers ranging from 210 to 840 and constant heat fluxes from 400.0 to 800.0 W/m^2. The simulations show that the heat transfer increases with heat flux and decreases with Reynolds number. Furthermore, the mechanisms of heat transfer enhancement of supercritical CO2 fluid are identified.